Elevated Plasma microRNA-105-5p Level in Patients With Idiopathic Parkinson’s Disease: A Potential Disease Biomarker - Yang, Zhaofei; Li, Tianbai; Cui, Yanhua; Li, Song; Cheng, Cheng; Shen, Bairong; Le, Weidong (Frontiers in Neuroscience, 2019)
Parkinson’s disease (PD) is the second most common neurodegenerative disease, which is still lack of biomarker to aid the diagnosis and differentiate diagnosis in early stage of the disease. microRNAs (miRNAs) are small and evolutionary conserved non-coding RNAs that are involved in post-transcriptional gene regulation and several miRNAs have been proposed to be potential biomarkers in several diseases. In the present study, we screened miRNAs through network vulnerability analysis to evaluate their possibility to be PD biomarkers. We first extracted miRNAs that were differentially expressed between PD and healthy controls (HC) samples. Then we constructed the PD-specific miRNA-mRNA network and screened miRNA biomarkers by a new bioinformatics model. With this model, we identified miR-105-5p as putative biomarker for PD. Moreover, we measured miR-105-5p levels in the plasma of patients with idiopathic PD (IPD) (n=319), neurological disease controls (NDC, n=305) and HC (n=273) by reverse transcription real-time quantitative PCR (RT-qPCR). Our data clearly demonstrated that the plasma miR-105-5p level in IPD patients was significantly higher than those of HC (251%, p < 0.001) and NDC (347%, p<0.001). There was no significant difference in miR-105-5p expression between IPD patients with or without anti-PD medications. Interestingly, we found that plasma miR-105-5p expression level may be able to differentiate IPD from parkinsonian syndrome, essential tremor and other neurodegenerative diseases. We believe that change in plasma miR-105-5p level is a potential biomarker for IPD.